Tourism and representation of culture: cultural identity and resistance in Andean communities of Cusco - Pérez Galán, Beatriz (2006)
The meaning of a type of theatrical representations on the preHispanic past –which have become quite popular all over Latin America in recent years– is explored in this paper as one of the main attractions for cultural tourism in the region. In Peru, these representations are known as “raymis” (the Quechua word for “festivals”). From an anthropological perspective, the relevance of studying these festivals is twofold: first, because given that tourism is the basis of the local political economy developed in wide areas of the “Sacred Valley of the Incas” (Cuzco), the industry of tourism has an active role in producing an ethnical discourse that is locally elaborated by the political and intellectual elite of Cuzco (the so-called “incanistas”) and globally consumed by tourists, natives, institutions, etc. Second, because these representations involve the participation of traditional authorities (the Mayors or “varayoqkuna”) as the political representatives of their communities in the staging of rituals for tourism. The hypothesis guiding this research suggests that, in the context of the post-colonial situation characterizing the insertion of peasant communities to the Peruvian society, the participation of “authentic” natives in these representations for tourism may be interpreted as an example of the political negotiation of indigenous groups vis-à-vis foreign powers.